2019
DOI: 10.1111/jfd.13076
|View full text |Cite
|
Sign up to set email alerts
|

Blood and liver biopsy for the non‐destructive screening of tilapia lake virus

Abstract: Detection of tilapia lake virus (TiLV) in tilapines is mainly from visceral organs of killed fish. However, lethal sampling might not be viable to broodstock and economically important ornamental cichlids. To contribute towards screening of the virus in asymptomatic infected fish, a subclinically infected population of Nile tilapia adults obtained from a local farm was preliminarily tested to compare different non‐lethal sampling methods, for example liver biopsy, gill biopsy, fin clip, mucus, faeces and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
3
20
0
2
Order By: Relevance
“…Detection of SDDV in multiple types of samples (seven destructive and three non-destructive) implied that SDDV infection is systemic during a clinical disease outbreak as previously suggested (Sriisan et al, 2020). Moreover, the presence of the virus in blood and mucus of all tested samples suggested that infected fish (both clinically sick and subclinical) from a disease outbreak can shed the virus to both systemic and mucosal systems similar to that of other viruses in finfish such as TiLV in tilapia (Chiamkunakorn et al, 2019;Liamnimitr et al, 2018) and ISAV in salmon (Aamelfot et al, 2015;Giray et al, 2005). The active viruses in the mucus might likely be able to be released into the cultured water and horizontally transmitted to other fish in the same population through direct contact or ingestion.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Detection of SDDV in multiple types of samples (seven destructive and three non-destructive) implied that SDDV infection is systemic during a clinical disease outbreak as previously suggested (Sriisan et al, 2020). Moreover, the presence of the virus in blood and mucus of all tested samples suggested that infected fish (both clinically sick and subclinical) from a disease outbreak can shed the virus to both systemic and mucosal systems similar to that of other viruses in finfish such as TiLV in tilapia (Chiamkunakorn et al, 2019;Liamnimitr et al, 2018) and ISAV in salmon (Aamelfot et al, 2015;Giray et al, 2005). The active viruses in the mucus might likely be able to be released into the cultured water and horizontally transmitted to other fish in the same population through direct contact or ingestion.…”
Section: Discussionsupporting
confidence: 51%
“…Pectoral fin can be used for detecting infectious hematopoietic necrosis virus (IHNV) in rainbow trout (Dhar et al, 2008). Similarly, non-destructive sampling methods using blood and liver biopsy samples were used for detection of tilapia lake virus (TiLV) in subclinically infected tilapia, while mucus was used for virus detection in clinically sick fish by molecular diagnostic assays (Chiamkunakorn et al, 2019;Liamnimitr et al, 2018).…”
mentioning
confidence: 99%
“…Different species of wild tilapia, comprising Sarotherodon galilaeus , Tilapia zilli , Oreochromis aureus and Tristamellasimonis intermedia, are also susceptible to TiLV (Eyngor et al., 2014). Besides tilapia, natural infection of TiLV has been shown in giant gourami ( Osphronemus goramy ) (Chiamkunakorn et al., 2019). Similar to natural infection, tilapia lake virus disease (TiLVD) could be reproduced in different species of tilapia and giant gourami under laboratory‐challenged conditions (Behera et al., 2018; Eyngor et al., 2014; Jaemwimol et al., 2018; Tattiyapong, Dachavichitlead, & Surachetpong, 2017).…”
Section: Tilapia Is the Main Host Of Tilv But Other Fish Species Alsomentioning
confidence: 99%
“…Apart from the tissues mentioned above, fish mucus has been tested for TiLV detection as a non‐lethal sampling procedure (Liamnimitr et al., 2018). Furthermore, a recent study showed that blood and liver biopsy could also be used for non‐destructive screening for TiLV (Chiamkunakorn et al., 2019). To detect TiLV genomic RNA, different RT‐PCR and RT‐qPCR protocols have been developed for TiLV.…”
Section: Diagnosis Of Tilvmentioning
confidence: 99%
“…So far, there are 16 countries that reportedly confirmed detection of TiLV (Jansen et al 2019; Surachetpong et al 2020), but a wider geographical spread has been hypothesized due to active movements of live tilapia with other countries (Dong et al 2017b). Waterborne spread of TiLV might also contribute to pathogen dissemination to new areas as well as transmission to other fish species (Chiamkunakorn et al 2019; Eyngor et al 2014; Jaemwimol et al 2018; Piamsomboon & Wongtavatchai 2021). Experimental evidences have already demonstrated that TiLV is both horizontally and vertically transmitted (Dong et al 2020; Eyngor et al 2014; Jaemwimol et al 2018; Yamkasem et al 2019).…”
Section: Introductionmentioning
confidence: 99%